Implementasi Pendidikan Karakter di Lingkungan Keluarga Masyarakat Sebauk, Kota Tanjungpinang - Abdul Malik; Dodi Dahnuss; Isnaini Leo Shanty (Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2019)
This community service activity aims at socializing the implementation of character education to families in Sebauk community and training families in Sebauk community on how to implement character education. The approach was socialization and implementation through lecture, discussion, and training the family members. The result of this activity was the increase of knowledge, understanding, skills, and attitudes of Sebauk community about the eighteen character values ​​that must be implemented in educating children in each Sebauk family.